Handbook of Human Resource Management in Government - Stephen E. Condrey, Editor (Jossey-Bass A Wiley Imprint, 2005)
Over the past several decades, the once staid field of public personnel administration has emerged as the rapidly changing field of human resource management. Although some may consider this a mere difference in nomenclature, court decisions concerning test validation and employee rights, legislation such as the Americans with Disabilities Act of 1990, technological and demographic changes in the workplace, and political pressures for reform, reinvention, outsourcing, decentralization, downsizing, and privatization have thrust the human resource manager into a pivotal position in rapidly changing governmental organizations. These changes have transformed personnel administration from an insulated administrative function performed in relative isolation to a crucial managerial function performed at many organizational levels. Since the first edition of this book was published in 1998, the field has continued to evolve. The most important changes are the increased calls for privatization of government services and the outsourcing of public human resource management functions. The states of Georgia and Florida have turned to more private-sector-oriented models to administer all or parts of their civil service systems. The newly formed federal Transportation Security Administration outsources most essential human resource management functions.